Magnetic Resonance Imaging Assessment of Intra-Articular Structures in the Canine Stifle Joint after Implantation of a Titanium Tibial Plateau Levelling Osteotomy Plate - Feichtenschlager, Christian; Gerwing, Martin; Failing, Klaus; Peppler, Christine; Kása, Andreas; Kramer, Martin; von Pückler, Kerstin H. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives To determine the effectiveness of magnetic resonance imaging (MRI) in the evaluation of anatomical stifle structures with respect to implant positioning after tibial plateau levelling osteotomy (TPLO) using a titanium plate.Methods Selected sagittal and dorsal sequences of pre- and postoperative MRI (1.0 T scanner) of 13 paired (n = 26) sound cadaveric stifle joints were evaluated. The effect of susceptibility artifact on adjacent anatomical stifle structures was graded from 0 to 5. The impact of implant positioning regarding assessment score was calculated using Spearman's rank correlation coefficient.Results Sagittal turbo spin echo (TSE)-acquired images enabled interpretation of most soft tissue, osseous and cartilage structures without detrimental effect of susceptibility artifact distortions. In T2-weighted TSE images, the cranial cruciate ligament and caudal horn of the medial meniscus could be evaluated, independent of implant position, without any susceptibility artifact in all specimens. T2-weighted fast field echo, water selective, balanced fast field echo and short tau inversion recovery were most markedly affected by susceptibility artifact.Clinical Significance In selected TSE sequences, MRI allows evaluation of critical intra-articular structures after titanium TPLO plate implantation. Further investigations with confirmed stifle pathologies in dogs are required, to evaluate the accuracy of MRI after TPLO in clinical cases in this context.
Keywords: titanium TPLO plate; susceptibility artifact; cranial cruciate ligament rupture; dog; magnetic resonance imaging